Faktor-Faktor Yang Mempengaruhi Kinerja Pengelolaan Sampah Di Pasar Banjarsari Kota Pekalongan - Rondiyah, -; Sulistiyani, -; Rahardjo, Mursid (Jurnal Kesehatan Masyarakat (Undip), 2014)
Market envionment is dirty and leaves garbage problems indicate less than optimal performance of waste management. The aims of this study are to evaluate solid waste management done by managers and many kind of influence in it. The methods used are quantitative desciption methodology. This research is using stratified random sampling which divided in to several homogeny groups amount in 94r respondents. The result of study, there are solid waste amount is 30,2 m3/day with the amount of solid waste which is in the service only 22 m3/day, there fore solid waste management performance only 72,85%. Of these conditions, solid waste management performance is still uneffective and far from the public expectation. Technical aspect such as placement, collection and transport of waste, awareness and the number of personal are influencing solid waste management performance, also lack of merchant participation in waste management and payment of levies, lack of capacity and the number of bins, lack of budget, and overseeing of waste management. Recommendations of this research is managers need to improve the area solid waste service in market by adding the number of personal, equipment, and need more socialization of solid waste management to the merchant